Mengukur Tingkat Literasi Teknologi Informasi dan Komunikasi Mahasiswa di Indonesia - Yonathan Anggian Siahaan; Fergyanto E. Gunawan (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
Nowadays, Information and Communication Technology (ICT) competence or literacy is an essential. The study measures the students' ICT literacy level and identify the influencing factors. It uses the People Capability Maturity Model (P-CMM) and Digital Competency frameworks. Data were collected using a questionnaire from a random sample of 400 students in Indonesia. The questionnaire used is a self-efficacy method, where respondents answer questions with self-reflection. The literacy level is the average of the responses. The influencing factors were evaluated by multivariate regression analysis. The results show that the level of ICT literacy of Indonesian students is at the level three (defined) of the five levels of the P-CMM framework, indicating that on average students understand and can apply ICT consistently to achieve their goals. This study found ICT literacy is influenced by the availability, accessibility, frequency of use, and duration of use of ICT infrastructure. Educational background, social science or exact, moderates the relationship between duration of use and levels of ICT literacy. In terms of competence, college majors have an effect on all areas of ICT competence (internet activities, communication and collaboration, digital content, security and problem solving). The level of parental education only has a significant effect on security competence and problem solving.